The Determinants of Rural Community Participation in Waste Bank: An Approach Using the Theory of Planned Behavior - Saleh, Muhammad; Alfiyah, Nilda; Susilawaty, Andi; Ikhtiar, Muhammad; Gafur, Abdul (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Waste management is a significant public health issue in rural areas, with most residents still disposing of waste on empty land in front of or behind their homes. Although proper management practices have been widely discussed in developing countries, limited studies are using comprehensive variables based on the Theory of Planned Behavior (TPB) to analyze the factors influencing community participation in Waste Bank programs. Therefore, this study aims to analyze the determinants of community participation in Waste Bank program in Paleteang District, Pinrang Regency, using TPB approach. The procedures were carried out using a quantitative survey with a cross-sectional design. Data were then collected from 396 participants using validated questionnaires, followed by analysis with Chi-Square tests and multiple linear regression. The results showed that subjective norms and perceived behavioral control significantly influenced community participation, with p-values of 0.025 and 0.005, and OR values of 4.183 and 8.250, respectively. Meanwhile, attitudes and satisfaction with local facilities had no significant influence. This showed the importance of social support and a sense of personal control in encouraging engagement. The results were expected to serve as a reference for policymakers in designing more effective and sustainable waste management programs in rural areas.